Structural Characteristics and Photocatalytic activity of TiO2/Si3N4 nanocomposite synthesized via plasma sputtering technique - Munif, Ali N.; Kadhim, Firas J. (Iraqi Journal of Physics, 2024)
This work evaluates a new TiO2/Si3N4 catalyst that was prepared by deposition of thin films of Si3N4 and TiO2 nanostructures on glass using lab made closed field unbalanced dc reactive magnetron sputtering technique. A highly-pure silicon sheet and titanium sheet were used as a sputtering target and gas mixture of (Ar: N2), (Ar∶O2) with mixing ratios of (50:50) for each were used to prepare TiO2/Si3N4 sample, respectively. This sample has been heat treatment.  The structure and morphology of the catalyst were determined by X-ray diffraction, Field-Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray (EDX) Spectroscopy, and Fourier transform infrared (FTIR) spectroscopy tests. The resultant nanocomposite sample was polycrystalline and there were no impurities in the investigated nanocomposite as revealed by XRD analysis. The absorption edge was found to be at 420 nm, as revealed by d UV-visible spectroscopy. The results obtained from the photodegradation of organic pollutants under a Xenon lamp indicate that TiO2/Si3N4 nanocomposite's photocatalytic activity is significantly more effective than TiO2 nanophotocatalyst.